Perbelanjaan Pembangunan Dari Perspektif Pusingan Belanjawan Di Peringkat Negeri Kedah - Rozita, Arshad (2001)
Development expenditure is one of the most important components in managing public budget. The main objective of this paper is to examine the development expenditure management practice embraced by the Kedah state government in achieving its budget management goals. This research is qualitative in nature and employs structured interview approach. Twenty-seven respondents participated in the structured interviews. These respondents were state executive council members, state assemblymen and officers from various departments, agencies and statutory bodies involved in the development expenditure management. In addition, informal interviews and texts analyses are also used in this research. Every approach in the qualitative research is utilized to explore the development expenditure management practice used in Kedah. This approach is adapted from several approaches used by researchers like Due and Friedlaender (1981), Lyden (1982), Walter (1985), Olt (1993), Lynch (1995), and Mikesell (1999). Approaches employed by the Malaysian researchers such as the National Institute of Public Administration (1991) and the Public Administration Progress Circular (1991), in particular, the Intergrated Project Management and Planning Cycle Model (PPPPB), were also used. The research demonstrates that in the planning phase, several processes involving the development sector selection, optional sector objectives and achievement measurement, identifying development projects that are progressive, conducting pilot study and probable study, and highlighting the benefit and risk justifications were carried out by the state government in managing the development expenditure. The findings for the approval phase indicate that the phase begins with the preliminary proposals and the selection of the appropriate proposal by the Economic Planning Committee. This will be followed by the approval of budget proposal by the State Govenunent Meeting Council (Exco) and will then be endorsed by the State Legislative Assembly. In the implementation phase, those involved in the phase will carry out pilot studies, appoint the appropriate contractor, follow the conditioned guidelines which are scheduled and documented and monitor and supervise the projects efficiently and methodically. The final phase, i.e. the evaluation phase involves the State Audit Department, the Public Account Committee (PAC) and the State Finance Office. Financial audit and performance audit will be conducted to evaluate a particular development project where the evaluation process starts off with the State Audit Department issuing observation letters to the relevant agencies and departments and dispatching the audit report to the State Legislative Assembly. The PAC will then be formed to investigate and to produce proposals and report. A follow up refinement will be made by the State Audit Department and the State Finance Office. To sum up, this research finds that the development expenditure management practice is well-organised and well-regulated. However, several areas that warrant future research have been identified by the researcher to enhance the state expenditure management. They are as follows: 1) Long term planning and half-term research, 2) to enhance expertise in the planning and implementation phase, 3) to reduce cost and time in the planning and implementation phase, 4) to overcome the land administration process problem in the implementation process, 5) to enhance efforts in evaluating development projects, 6) to provide finance management training, 7) to encourage investment incentives and 8) budget cycle approach.